2023
DOI: 10.3390/electronics12030515
|View full text |Cite
|
Sign up to set email alerts
|

BERT-Based Joint Model for Aspect Term Extraction and Aspect Polarity Detection in Arabic Text

Abstract: Aspect-based sentiment analysis (ABSA) is a method used to identify the aspects discussed in a given text and determine the sentiment expressed towards each aspect. This can help provide a more fine-grained understanding of the opinions expressed in the text. The majority of Arabic ABSA techniques in use today significantly rely on repeated pre-processing and feature-engineering operations, as well as the use of outside resources (e.g., lexicons). In essence, there is a significant research gap in NLP with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Furthermore, [42] tested a transfer-learning approach using Arabic-BERT-CRF for tasks T1 and T2 on a human-annotated Arabic dataset for ABSA. The experimental results demonstrated that the model exceeded the baseline model, which relied on conditional random fields (CRF) with features extracted using named entity recognition (NER), POS tagging, parsing, semantic analysis, and other recently proposed models such as AraBERT, MarBERT, and CamelBERT-MSA.…”
Section: ) Deep Learning Approachesmentioning
confidence: 99%
“…Furthermore, [42] tested a transfer-learning approach using Arabic-BERT-CRF for tasks T1 and T2 on a human-annotated Arabic dataset for ABSA. The experimental results demonstrated that the model exceeded the baseline model, which relied on conditional random fields (CRF) with features extracted using named entity recognition (NER), POS tagging, parsing, semantic analysis, and other recently proposed models such as AraBERT, MarBERT, and CamelBERT-MSA.…”
Section: ) Deep Learning Approachesmentioning
confidence: 99%
“…Another deep learning model for manipulating Arabic sentiments was presented in [49], where the data was collected based on three classes and then classified using the LSTM model to explore the results. One of the recent methods for extracting and detecting Arabic polarity text was proposed in [50], where transfer learning (TL) techniques were applied to aspect-based Arabic text. The authors proposed an architecture using the BERT model on the HAAD dataset to measure the approach's effectiveness, which showed high results.…”
Section: Machine Learning-based Approachmentioning
confidence: 99%
“…It is an important topic of interest and an active field of study in all languages, especially for languages that lack sufficient scientific research and resources, such as datasets, lexicons, corpora, and tools [2]. One of these languages is the Arabic language, where the progress in Arabic opinion mining does not fit with the substantial Arab world population, contributing to generating enormous amounts of Arabic data on the web [3][4][5]. The other challenges of the Arabic language, including being inherently complex and using dialects of Arabic, are also slowing research advancement [6].…”
Section: Introductionmentioning
confidence: 99%